Optimization of extraction process and antioxidant activity of total flavonoids from Aloe vera stir-fry products - ZENG Lingqin; GUO Jiangtao; LIU Jie; CHEN Zhengyuan; XU Jiahong (Shipin yu jixie)
Objective: To optimize the extraction process of total flavonoids from Aloe vera stir-fry products and investigate its antioxidant activity. Methods: Single factor test and response surface method were used to optimize the extraction process, The content of total flavonoids in Aloe vera raw and fried products from different areas was determined by UV spectrophotometry,The antioxidant activity was studied by DPPH·, ABTS+·, ·OH and FRAP methods, the correlation between total flavonoids yield and antioxidant activity was analyzed by Pearson correlation. Results: The optimal extraction conditions were as follows soaking time 3 h, ultrasonic time 15 min, ethanol volume fraction 60% and solid-liquid ratio 1∶10 （g/mL）. The content of total flavonoids in Aloe vera increased. The total flavonoids of Aloe vera raw and fried products from 8 producing areas had certain scavenging effect on four kinds of free radicals, and the concentration was positively correlated with that of Aloe vera, showing good antioxidant activity.Correlation analysis showed that antioxidant capacity was significantly correlated with total flavonoid yield. Conclusion: The optimized extraction process of total flavonoids from Aloe vera stir-fried products is reasonable and feasible, and has strong antioxidant activity.